Konsep Ketertiban Umum dalam Hukum Perdata Internasional: Perbandingan Beberapa Negara Civil Law dan Common Law - Sri Wahyuni (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2014)
This article discusses about public order in the Private Internationale Lawcontext, relating to the acceptance to the foreign law in a country. Every country has thepublic order although they are different in concept and implementation. This publicorder principle is important as an emergency filter when a country faces a foreign law. Ifthe foreign law is incompatible to the public policy of the country, the foreign law can beignored. The country may use it own national law. The implementation of public orderprinciple relates to the other principles in the Private International Law, such asnationality, domicile and vested rights principles.